Metabolomics Reveals Aging-associated Attenuation of Noninvasive Radiation Biomarkers in Mice: Potential Role of Polyamine Catabolism and Incoherent DNA Damage-repair - Manna, Soumen K; Krausz, Kristopher W; Bonzo, Jessica A; Idle, Jeffrey R; Gonzalez, Frank J (Journal of proteome research, 2013)
Development of methods for rapid screening and stratification of subjects after exposure is an integral part of countermeasures against radiation. The potential demographic and exposure history-related heterogeneity of exposed populations warrants robust biomarkers that withstand and reflect such differences. In this study, the effect of aging and repeated exposure on the metabolic response to sublethal irradiation was examined in mice using UPLC–ESI–QTOF mass spectrometry. Aging attenuated postexposure elevation in excretions of DNA damage biomarkers as well as N 1-acetylspermidine. Although N 1-acetylspermidine and 2′-deoxyuridine elevation was highly correlated in all age groups, xanthine and N 1-acetylspermidine elevation was poorly correlated in older mice. These results may reflect the established decline in DNA damage-repair efficiency associated with aging and indicate a novel role for polyamine metabolism in the process. Although repeated irradiation at long intervals did not affect the elevation of N 1-acetylspermidine, 2′-deoxyuridine, and xanthine, it did significantly attenuate the elevation of 2′-deoxycytidine and thymidine compared to a single exposure. However, these biomarkers were found to identify exposed subjects with accuracy ranging from 82% (xanthosine) to 98% (2′-deoxyuridine), irrespective of their age and exposure history. This indicates that metabolic biomarkers can act as robust noninvasive signatures of sublethal radiation exposure.